Mathematical Methods for Solar Chimney Analysis - Strobel, C.S.; Moura, L.M.; Mariani, V.C. (Journal of Technology Innovations in Renewable Energy, 2018)
Solar Chimney Power Plants (SCPP) – also known as Solar Updraft Power Plants – consists in a structure composed by a glass collector, placed in a few meters from the ground, with a chimney in its center, in order to promote a pressure differential and consequently a heated air flow. On the bottom of the chimney, a turbine convert the kinetic energy from the heated airflow in electric power. Many mathematical and numerical methods for predict the performance of this kind of renewable energy plant have been conducted, but always with a divergence among them. The main objective of this work is to compare the mathematical methods of evaluation the overall performance, as well to propose a more accurate mathematical method, comparing all results with Manzanares Plant and other methods in the literature. Two approaches were studied and then modified: one based on continuity and momentum equation and the other based on the sum of all pressure drops along the system. The main reasons of the difference between the models analyzed are highlighted. The results shows that one of the proposed methods leads to a divergence of only 1.3% when compared to Manzanares pilot plant, i.e., with an excellent agreement with experimental data.